Composition and Formation Kinetics of Erosion Products of the Metallic Charge in an Electric-Discharge Reactor; Russian Journal of Applied Chemistry; Vol. 78, iss. 9 - Danilenko N. B. Nina Borisovna; Savel'ev G. G.; Yavorovsky N. A. Nikolay Aleksandrovich; Yurmazova T. A. Tatyana Aleksandrovna; Galanov A. I. Andrey Ivanovich; Baluhtin P. V. Peter Valerievich (2005, 2005)
Title screen